Antisera to scrapie-associated fibril protein and prion protein decorate scrapie-associated fibrils. - Merz, P A (1987)
Scrapie-associated fibrils (SAF) are an infection-specific structure observed in the unconventional-agent diseases. Polyclonal antisera raised to scrapie proteins were used to test the antigenic relationship between purified fibrils and SAF isolated from non-protease-treated synaptosomal-mitochondrial preparations. The experimental design utilized fibrils from scrapie strain 263K-infected hamsters, scrapie strain 139A-infected mice, and scrapie strain ME7-infected mice. Preparations were examined by negative-stain immune electron microscopy and Western blot analysis of the polypeptides. Fibrils and polypeptides from each preparation reacted with a rabbit antiserum raised to each of the following: hamster 263K prion protein (PrP 27-30), hamster 263K SAF protein, and mouse ME7 SAF protein. Immune electron microscopy and Western blot analysis revealed similar antigenic relationships among the three scrapie antisera. Thus, fibrils and polypeptides can be considered to be the same in each preparation. No reactivity of the fibrils was observed with antisera raised to Alzheimer neurofibrillary tangles or a synthetic peptide of cerebrovascular amyloid. Thus, the fibrils observed in purified preparations share structural and antigenic similarities plus biochemically related peptides with SAF present in non-protease-treated preparations.